The Impact of COVID-19 on Banking Sector Returns, Profitability, and Liquidity in South Africa - Peerbhai, Faeezah; Kunjal, Damien (International Journal of Economics and Financial Issues, 2024)
The COVID-19 pandemic, which initially started as a health crisis, has had widespread economic impacts on various industries in the global economy. The banking sector, in particular, was significantly impacted by fiscal and monetary responses which were implemented to reduce the closure of several businesses and stabilize markets. Given that banks are regarded as systemically important financial institutions, this heightened uncertainty increased the possibility of a financial crisis because instabilities in the banking sector could have further detrimental effects on national and global economies. Therefore, the objective of this study was to explore the effect of the COVID-19 pandemic on the South African banking sector. To achieve this objective, the study analysed the returns, profitability, and liquidity of banks listed on the Johannesburg Stock Exchange using a panel regression approach. Together, the results of the study revealed that the profitability and liquidity of banks were negatively impacted by the COVID-19 pandemic, however, the excess bank stock returns generated by investors were not affected. These findings may serve as reference to policymakers when developing policies which regulate the banking sector in order to improve performance and ensure liquidity during periods of increased market uncertainty.